2006
DOI: 10.1093/nar/gkl727
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dysfunction associated with the human mitochondrial 3302A>G mutation in the MTTL1 (mt-tRNALeu(UUR)) gene

Abstract: The gene encoding mt-tRNALeu(UUR), MT-TL1, is a hotspot for pathogenic mtDNA mutations. Amongst the first to be described was the 3302A>G transition which resulted in a substantial accumulation in patient muscle of RNA19, an unprocessed RNA intermediate including mt-16S rRNA, mt-tRNALeu(UUR) and MTND1. We have now been able to further assess the molecular aetiology associated with 3302A>G in transmitochondrial cybrids. Increased steady-state levels of RNA19 was confirmed, although not to the levels previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 41 publications
(49 reference statements)
4
30
0
Order By: Relevance
“…Changes in TFAM concentration seem to be important for regulating rates of mitochondrial transcription in vitro and in vivo, as demonstrated by studies on transcription in organello and cell lines (24,25). However, besides being a transcription factor, TFAM is also an important component of mitochondrial nucleoids and is essential for the maintenance of mtDNA (26 -28).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in TFAM concentration seem to be important for regulating rates of mitochondrial transcription in vitro and in vivo, as demonstrated by studies on transcription in organello and cell lines (24,25). However, besides being a transcription factor, TFAM is also an important component of mitochondrial nucleoids and is essential for the maintenance of mtDNA (26 -28).…”
Section: Resultsmentioning
confidence: 99%
“…This variant caused the severe respiratory chain complex I deficiency and lowered complex IV activity. Moreover, a significant reduction in the steady-state level of tRNA Leu(UUR) was observed in cell carrying this variant [20]. Studies concerning the functional role of A3302G variant showed that it led to abnormal processing of the mt-16SrRNA-tRNA Leu(UUR) -ND1 precursor RNA [21].…”
Section: Discussionmentioning
confidence: 99%
“…To maintain charging of the tRNAs with amino acid and separate tRNA from amino-acylated tRNA, RNA was isolated and subjected to electrophoresis under acidic conditions on long gels, as described previously [16]. Regions of mtDNA encompassing mitochondrial tRNA genes were amplified from DNA from the 143B cells by PCR and used as probes.…”
Section: Northern-blot Analysismentioning
confidence: 99%
“…Purified PCR products (QIAquick PCR purification columns; Qiagen, Hilden, Germany) were radiolabelled with [α-32 P]dCTP (5000 Ci/mmol; Hartmann Analytic) using a random-primed DNA labelling kit (Roche Applied Science, Mannheim, Germany), and unincorporated nucleotides were removed from the labelling reactions by gel filtration through ChromaSpin columns (Clontech, Heidelberg, Germany). Prehybridization, hybridization and analysis of the data by phospho-imaging was carried out as described previously [16]. The two bands corresponding to amino-acylated and non-acylated tRNA were identified by comparison of native with alkali-treated de-acylated RNA samples from 143B cells and quantified individually in order to estimate the degree of loading with amino acid.…”
Section: Northern-blot Analysismentioning
confidence: 99%